(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The proposed study presents an investigation of the influence of the wearing and the belt drive parameters’ changes over the forced torsional vibrations in the saw unit of a wood shaper. These changes affect the elastic and damping coefficients of the machines’ elements. The research is done on the base of a concrete mechanic-mathematical model for numerical investigations of the torsional vibrations of a wood shaper’s saw developed by the authors. The main features in the construction of the wood shapers are rendered an account in this model. Work’s conditions in the practice are modeled with the variable moments on the drive electric motor and the wood shaper’s saw. The conclusions based on the numerical investigations are confirmed by the real conditions. The results of the whole investigation are applicable to the direct well-founded recommendations concerning the operation of these machines. These recommendations are important for the increase of the accuracy and quality wood shapers’ production. At the same time the results of this research are useful for technical diagnostics of the wood shapers.